Analysis Handling Vegetables on Part Receiving and Preparation at PT. Mapan Sukses Sejahtera - Martiza Alea Ramadhany; Lilis Sulandari; Aisha Nurin Kamiliya (Universitas Negeri Surabaya, 2025)
Vegetables are food ingredients that come from parts of plants such as leaves, stems and flowers. on vegetables, vegetables Also is material Which easily damaged. Handling must be appropriate from the receiving stage to the preparation stage . In one of the food industries, PT. Mapan Sukses Sejahtera, food processing and distribution has its own standards and procedures for handling raw materials, including vegetables. Handling Which not enough appropriate Also can causing cross-contamination, waste of ingredients, and a decrease in the nutritional value and freshness of vegetables. Objective: This study aims to analyze the handling system implemented at PT. Mapan Sukses Sejahtera for several types of vegetables from the receiving stage and also from the preparation stage . Method: This research uses a qualitative descriptive approach through direct observation, interviews with internal parties. company (staff Receiving , staff Quality Control , And preparation staff ), as well as studies documentation report reception goods, goods delivery procedures. Results: The results of the study show that PT Mapan Sukses Sejahtera has implemented a good vegetable handling system, by implementing good procedures in receiving vegetables. Which in accordance provision, sorting vegetables Which Good, and packaging of vegetables in the receiving section , as well as cleaning and washing clean vegetables, storing vegetables in the preparation section . Conclusion: System handling vegetables on part Receiving is carried out systematically through document checks, verification of the type and quantity of ingredients, and quality checks by Quality Control . Unsuitable vegetables are returned to the supplier , while suitable vegetables are packaged, labeled, and shipped using chiller trucks . Meanwhile, in the receiving section, vegetables are cleaned, weighed, and cut as needed. Tools such as knives and cutting boards are separated to prevent cross-contamination. Ingredients are stored in closed bowls in cold storage and monitored regularly by supervisors